Influence of Bagasse Ash on Compaction and Strength Properties of Soil Mixed with Sisal Fiber - Renu, Vinod K. Sonthwal (International Journal of Advanced Science and Technology, 2020)
Waste disposal poses a serious threat to a well-organized environment. Since this can cause harmful effects on society, it is also necessary to eliminate it effectively. To solve this problem in modern times, the utilization of wastes for stabilization of soil has built an importance as a efficient measure of managing waste produced by various sectors. This document is based on local soil testing with such waste material and ecological natural fiber. From this study, we are able to know how wastes can be utilized for stabilization of weak soil. This study is based on significant laboratory attempts that were done to study the use of agricultural, industrial and natural fiber residues to improve the strength characteristics of the compressible clay which was obtained from the location of Airport Road, Mohali, Punjab, India. In this study which isintended to examine aptness of bagasse ash and sisal fiber to strengthen compressible soil. Toclassify the soil we determined consistency limits, compaction test for the determination of MDD and OMC, to study the strength of soil we determinedthe UCS and soaked CBR tests with BA in the proportion of 2%, 4%, 6% and 8% and sisal fiber in with varying length of 2mm, 4mm and 6mm inthe proportions of 1%, 1.5% and 2% by weight of  soil.